Multiculturalism and Interculturalism: a systematic review with emphasis on School Psychology - Fonseca, Thaisa da Silva (2025)
This systematic literature review, based on the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) recommendation, investigated national scientific production on School Psychology, Multiculturalism, and Interculturalism from 2012 to 2023 in six databases and from 1993 to 2023 in 17 books belonging to a reference collection in the field. The results, derived from articles, theses, and dissertations found in the databases, indicated that of the five materials related to school psychology, one thesis discussed the relevance of the field's contributions to intercultural scenarios. Of the 180 chapters, five were related to the subject under investigation, and of these, one contemplated a more in-depth debate on the issue. Consequently, the extant literature on the subject reviewed herein contains elements that can support the proposition of broad and contextualized actions to be developed by school psychologists in these contexts.